Nutritional Effects on Dairy Cattle Fertility - Alragubi. S. M.; Dr. Naser Estuty (International Journal for Research in Applied Sciences and Biotechnology, 2021)
Dairy cow fertility has declined in recent decades, coincidental with large increases in milk production. The problem is often considered being nutritional and can be corrected through dietary adjustment. The interaction between nutrition and reproduction is poorly tuned, and study results are often contradictory. Nutrition is an important component of successful reproduction, but dietary change to improve pregnancy rates is complicated, and merely offering pastured cows a supplement is unlikely to result in large effects, say authors. The effect of energy balance, carbohydrate type, protein and fat on reproductive outcomes will be considered.